Shelf life of embryo culture media: Buffering potential of media apparently not the determining factor - Amjad Hossain; Collin Osuamkpe; Safina Hossain; John Phelps (Middle East Fertility Society Journal, 2010)
Objective: To investigate if the buffering power of embryo culture media is compromised by expiration. Design: Buffering potential of expired culture media was evaluated by measuring pH values. Setting: Fertility Laboratory, the University of Texas Medical Branch, USA. Materials and methods: The pH of expired culture media were measured and compared with those of unexpired ones in three experimental conditions: (1) pre-incubation, (2) CO2 incubation and (3) post-incubation. Sequential media, comprising Quinn's advantage fertilization, cleavage and blastocyst media (Sage assisted reproduction products Inc.), were used. The media were divided into expired and unexpired groups, based on the manufacturer's indicated expiration dates. The unexpired group was evaluated in their original condition (first time opened). The expired media bottles underwent more than one opening. The pH of the media was measured sequentially in conditions 1, 2 and 3. Results: The expired media (30–390days) displayed significantly (p<0.05) different pH values compared to unexpired media in pre-incubation condition. However, expired media were capable of yielding similar pH values (p⩾0.23) to those of the corresponding unexpired controls in CO2 incubation as well as post-incubation suggesting that the buffering capacity of the media is apparently not affected by expiration. Conclusion: Time-dependent nutrient depletion, not the weakening of the buffering system, is probably the determining factor in setting the shelf life of the culture media.